Multiple large osteolytic lesions in a patient with systemic mastocytosis: a challenging diagnosis. Issue 12 (25th October 2017) - Bonifacio, Massimiliano; Zanotti, Roberta; Guardalben, Emanuele; Mimiola, Elda; Scognamiglio, Francesca; Perbellini, Omar; De Matteis, Giovanna; Escribano, Luis; Bonadonna, Patrizia; Grigolato, Daniela; Bissoli, Sergio; Parisi, Alice; et al.
Key Clinical Message: Patients with advanced variants of Systemic Mastocytosis may develop destructive bone lesions when massive mast cell (MC) infiltrates are present. Finding of large osteolyses in indolent systemic mastocytosis, typically characterized by low MC burden, should prompt investigations for an alternative explanation. Abstract : Patients with advanced variants of Systemic Mastocytosis may develop destructive bone lesions when massive mast cell (MC) infiltrates are present. Finding of large osteolyses in indolent systemic mastocytosis, typically characterized by low MC burden, should prompt investigations for an alternative explanation.